A STUDY ON THE ABILITY OF THE THIRD YEAR STUDENTS OF MAN 2 PEKANBARU IN COMPREHENDING NEWS ITEM TEXTS - Windi Mei Syaputri; Supriusman Supriusman; Dahnilsyah Dahnilsyah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This descriptive research aims to discover the ability level of the third year students of MAN 2 Pekanbaru in comprehending news item texts. The population of this research was all of the third year students of MAN 2 Pekanbaru, academic year 2019/2020. The numbers of sample were 25 students which were chosen by using cluster random sampling technique. The data were collected by means reading comprehension test in the form of multiple choices by giving 8 news item texts with 40 multiple choice items. The results of the data analysis showes that the mean of the students’ score in compreheneding news item texts is 70.88. It can be concluded that the ability of the third year students of MAN 2 Pekanbaru in comprehending news item texts is in good level. Based on the result of the students’ scores in each of reading comprehension component, the lowest component of reading comprehension is the ability in finding the meaning of vocabulary 52.00 and the highest one is the ability in finding inferences 80.00.Key Words: Study, Ability, News Item Text.